Pengaruh Kualitas Pelayanan Publik dan Service Recovery Terhadap Kepuasan Masyarakat Pada Mal Pelayanan Publik (MPP) Kota Tarakan - Hasanah, Nurjannatul; Islami, Rahmi Nur; Dewi, Yuliana (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This research aims to examine the influence of the quality of public services and service recovery provided by the Public Service Mall on the satisfaction of the people of Tarakan City. This research was conducted in the Tarakan City Public Service Mall building using a quantitative approach through a survey method with a research instrument in the form of a questionnaire. Sampling was carried out using non-probability sampling techniques using a purposive sampling method of 170 respondents. Data quality testing in this research was carried out through validity testing, reliability testing and classical assumption testing, while hypothesis testing was carried out through multiple regression analysis and t test. Based on hypothesis testing carried out using the Statistical Product and Service Solution (SPSS) version 25.0 program, it shows that: First, the service quality variable has a positive effect on public satisfaction. Second, the service recovery variable has a positive effect on community satisfaction.